2018
DOI: 10.2478/anre-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in healthy Syrian women measured by dual energyX-ray absorptiometry

Abstract: Assessment of bone mineral density (BMD) using dual energy X-ray absorptiometry (DXA) technique is considered as a standard technique for diagnosing osteopenia and osteoporosis and evaluating the severity of such diseases. Numerous studies have demonstrated the necessity to establish an ethnicspecific reference data for Bone mineral density measurements. Such data are lacking for the Syrian population. The objectives of this study are (1) to establish BMD reference values in a group of healthy Syrian women usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…In our results, 145 females were examined by DEXA scan, of whom (55.17%) were diagnosed as abnormal bone mineral density and (44.83%) were with normal bone mineral density results. This is in accordance with other studies in Saudi, Syrian and Iranian women, [23][24][25][26]. While this is in discordance with Brazilian study, 36.5% of women had normal BMD, and 63.5% were diagnosed with abnormal BMD [27].…”
Section: Discussionsupporting
confidence: 91%
“…In our results, 145 females were examined by DEXA scan, of whom (55.17%) were diagnosed as abnormal bone mineral density and (44.83%) were with normal bone mineral density results. This is in accordance with other studies in Saudi, Syrian and Iranian women, [23][24][25][26]. While this is in discordance with Brazilian study, 36.5% of women had normal BMD, and 63.5% were diagnosed with abnormal BMD [27].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the prevalence of this disease in the Middle East is 24.4%, with Saudi Arabia having the highest prevalence and Kuwait having the lowest [ 4 ]. Additionally, as concluded by Mohammed Bakir et al in their study on 951 Syrian women, 23.68% were diagnosed with osteoporosis in the lumbar spine, while 13.1% had evidence of osteoporosis in the neck of the femur [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Saudi Arabia has the highest prevalence, with 32.7%, while Kuwait has the lowest with 15.1% [ 1 ]. A study from Syria reported that 36.84% of the studied women, which belonged to the age group between 50 and 59, were diagnosed with osteopenia in the lumbar spine and in the femoral neck in 68.42%, while osteoporosis was diagnosed in the lumbar spine in 23.68% of cases and 13.10% in the femoral neck [ 6 ]. 33.3% of women and 16.6% of men will sustain a hip fracture by their ninth decade [ 1 ].…”
Section: Introductionmentioning
confidence: 99%